FILM INDUSTRY TRENDS IN SULAWESI: AN ECONOMY-BASED CULTURE AS A NEW ECONOMIC FORCE (Proceeding of the International Conference on Arts and Humanities, 2018)
Indonesia's wealth potential is very large and wide, one of which is cultural diversity. Surely this is likely to encourage the competitiveness of the Indonesian nation in the future by prioritizing creativity and innovation in national development to optimize the potential wealth of its possessions. In this research, the researcher wants to expose the trend of film industry in Sulawesi which most of the film take local title close to daily, or local culture. Such as a movie uangpanai’ prove that local films still get a warm place in the people of Indonesia. This film became the first regional film that can penetrate Box Office Indonesia. The film gets a new stage, Dozens of production houses (PH), acting classes, and a number of movie titles keep popping up so that opens up many job opportunities. So that later Indonesia will no longer rely on exports of raw materials, but will also be able to export high value-added products. Creativity and innovation will also make the local cultural heritage and wisdom contribute greatly not only to the national economy but also to improving the image of the Indonesian nation in the eyes of the international world. The two main approaches used by this journal in the development of the national creative economy, the national collaborative approach, namely the collaboration between industrial sectors, universities, government, business actors, and the creative community; As well as strategic focus approach, that is, the government must be bold in determining the focus of creative industry development in terms of determining the focus of industry sector and creativity-based areas that will be developed.
Keywords: Industry; Economy; Culture